Pattern of Demand for Money - Ahmad Berlian; Liliana Liliana; Syaipan Djambak; Sri Andaiyani; Zulkarnain Ishak; Muhammad Syrod Saleh; Eka Rostartina; Nazeli Adnan; Fachrizal Bahri (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2017)
In the activity of the modern economy, the availability of money as a means of transaction is very important, because with the money as a means to pay consumers can easily to get the basic material needs are required, the manufacturer can provide the raw materials of labor for production, and distributors can obtain a variety of merchandise to be delivered at the end consumer. The pattern of use of money is influenced by the attitude of the public in the transaction. Researchers assume, that there are differences among communities, either by group differences in income, educational differences, ethnic differences, differences in profession, and perhaps even religious differences embraced. So as to provide information to the monetary authorities, to enrich the theory of demand for money based economic agents in Indonesia, and for the application of the theory of demand for money, the researchers felt the need to study patterns of use of money. Qualitative research, in addition to knowing whether the variables that affect the demand for money as the above theory is still relevant for economic actors in Indonesia at this time, or even are new variables, as well as the motive of money demand.